Colorectal Cancer Presenting as Single Pulmonary Hilar Lymph Node Metastasis - Ahmed M. Habib; Xenophon Kassianides; Samuel Chan; Mahmoud Loubani; Syed Qadri (Case Reports in Surgery)
Colorectal carcinoma is the second biggest cancer responsible for mortality. Lung metastasis is the commonest, following the liver. It is not uncommon to perform pulmonary metastasectomy and identify mediastinal metastasis. Previous studies have identified incidental lymph node involvement following routine mediastinal lymph node clearance in 20–50% of cases. However, solitary intrathoracic lymph node metastasis is exceedingly rare. Even when present, it is usually metachronous. In our case, we present an exceedingly rare case whereby the intrathoracic lymph node metastasis is solitary, not accompanying pulmonary disease and with no liver metastasis. We also review the evidence for mediastinal lymphadenectomy in the literature.